2002
DOI: 10.1007/s00216-002-1564-8
|View full text |Cite
|
Sign up to set email alerts
|

Separation and determination of vanadium in fertiliser by capillary electrophoresis with a light-emitting diode detector

Abstract: A method has been developed for determination of vanadium, as an anionic ternary complex of vanadium(V) with 4-(2-pyridylazo) resorcinol (PAR) and hydrogen peroxide, after separation by capillary electrophoresis (CE). The optimum conditions for the formation of the ternary complex were acetate buffer (3 mmol L(-1)) at pH 6 containing 0.15 mmol L(-1) PAR and 7.1 mmol L(-1) H(2)O(2). The CE separation was conducted using 15 mmol L(-1) acetate buffer at pH 6 as the background electrolyte; the separation potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…The comparison of the metal concentrations obtained at October 14th with the average concentrations obtained in three remaining samplings within the same site revealed 14-17 times increased concentrations of Ti and Cr, and 2-4 times increased concentrations of Co, Cu, Rb, K, and V. The presence of corn fields in the immediate vicinity of the last two sampling sites indicated that temporary concentration increases of specific metals could be the consequence of sporadic emissions or leaching of the waste manure in the river water. It can be further corroborated by the fact that K 2 O, copper sulfate, Co, and Ti are commonly used ingredients in fertilizers (Anke 2004b;Momčilović 2004;Schrauzer 2004;Anke and Seifert 2004), whereas some of the metals which were found increased are common contaminants of NPK fertilizers, e.g., V and Rb (Vachirapatama et al 2002;Senesi et al 1983). The number of enterococci in the river water at the sites 7 and 8 was also appreciably increased at October 14th (approximately 50 times; Fig.…”
Section: Point Source Water Contaminationmentioning
confidence: 91%
“…The comparison of the metal concentrations obtained at October 14th with the average concentrations obtained in three remaining samplings within the same site revealed 14-17 times increased concentrations of Ti and Cr, and 2-4 times increased concentrations of Co, Cu, Rb, K, and V. The presence of corn fields in the immediate vicinity of the last two sampling sites indicated that temporary concentration increases of specific metals could be the consequence of sporadic emissions or leaching of the waste manure in the river water. It can be further corroborated by the fact that K 2 O, copper sulfate, Co, and Ti are commonly used ingredients in fertilizers (Anke 2004b;Momčilović 2004;Schrauzer 2004;Anke and Seifert 2004), whereas some of the metals which were found increased are common contaminants of NPK fertilizers, e.g., V and Rb (Vachirapatama et al 2002;Senesi et al 1983). The number of enterococci in the river water at the sites 7 and 8 was also appreciably increased at October 14th (approximately 50 times; Fig.…”
Section: Point Source Water Contaminationmentioning
confidence: 91%
“…A study of solute-wall interactions using this system was also performed [24]. Vachirapatama et al [18] achieved direct detection of vanadium-PAR (4-(2-pyridylazo)resorcinol) complexes at 568 nm. LODs of 19 ppb were reported and analysis of vanadium in fertilizer samples was performed.…”
Section: Introductionmentioning
confidence: 98%
“…One approach at optimizing the potential benefits of using highly absorbing probes is to use a light source with better characteristics in the visible region. Light-emitting diodes (LEDs) have found some use for this purpose [13,[15][16][17][18] because they emit strongly in the visible region (and for some recent examples, also in the high-UV region [17]), have near monochromatic output, are highly stable, have long lifetimes, and are very affordable. Unfortunately, there are currently no commercially available LED-based detectors for CE.…”
Section: Introductionmentioning
confidence: 99%
“…The recent development of light-emitting diodes (LEDs) has been shown to offer considerable advantages over conventional light sources due to their superior stability and exceptionally low noise. We have made extensive use of LEDs in CE and our studies have shown that these two factors combine to provide a significant enhancement in sensi-tivity over conventional light sources [11][12][13][14][15][16][17][18]. In addition, LEDs are cheap, small and have an extended lifetime, thus enhancing their potential as light sources, particularly in the development of portable microfluidic systems.…”
Section: Introductionmentioning
confidence: 93%